The Right Setting of the Quaternion Calculus - Solanilla-Chavarro, Leonardo (Revista Tumbaga, 2012)
Quaternionic analysis, it is usual to persist in pointing out to their distinguished characteristics. It is our aim in this paper, by contrast, to set forth a natural (i.e. canonical) and rather comprehensive account of the quaternion calculus. Accordingly, we show that a proper notion of quaternionic derivative leads to the fundamental integral theorem which generalizes straightforwardly the better-known complex and real cases.